SRIKANDI IN THE DOCUMENTARY FILM: NUSANTARA DOCUMENTARY ASSOCIATION’S REKAM PANDEMI - Rembulan, Dara Bunga; Swaradesy, Rufus Goang (Seni Media Rekam ISI Surakarta, 2022)
Gender inequality persists in the documentary film genre. It is assumed that women in the documentary field face so many obstacles that it contributes to the shortage of female documentary filmmakers. This research aims to examine the potentials of female filmmakers in the TVRI's Pandemic Recording program. This study is qualitative descriptive research. The research subjects were female filmmakers who participated in the TVRI's Pandemic Recording program and selected a purposive sampling technique. The data collection techniques relied on structured interviews. The analysis was carried out through data reduction, data presentation, conclusion, and verification. The findings indicate that the selection of female filmmakers in TVRI's Pandemic Recording Omnibus program reflects the achievements and potentials of female filmmakers, including